2017
DOI: 10.1007/s00414-017-1548-z
|View full text |Cite
|
Sign up to set email alerts
|

The geometrical precision of virtual bone models derived from clinical computed tomography data for forensic anthropology

Abstract: Almost all European countries lack contemporary skeletal collections for the development and validation of forensic anthropological methods. Furthermore, legal, ethical and practical considerations hinder the development of skeletal collections. A virtual skeletal database derived from clinical computed tomography (CT) scans provides a potential solution. However, clinical CT scans are typically generated with varying settings. This study investigates the effects of image segmentation and varying imaging condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…No validation study exists to date for virtual measurements of the calcaneus compared to measurements on the dry bone. We do not however anticipate the error to exceed the acceptable threshold of 2mm that was reported for other skeletal elements [47][48].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…No validation study exists to date for virtual measurements of the calcaneus compared to measurements on the dry bone. We do not however anticipate the error to exceed the acceptable threshold of 2mm that was reported for other skeletal elements [47][48].…”
Section: Discussioncontrasting
confidence: 54%
“…One could argue that measurements taken on virtual models, as in our case, may introduce an error in the study as they are generally considered less reliable compared to measurements on the dry bone. Recent validation studies on the cranium/long bones [47] and pelvis [48] suggest that the measurement error on virtual bones does not exceed 2mm, which implies high reliability. No validation study exists to date for virtual measurements of the calcaneus compared to measurements on the dry bone.…”
Section: Discussionmentioning
confidence: 99%
“…Using different scanner types and software packages for volume data acquisition might have induced artefactual variance in the superimposed Landmark Dataset 1; we did not account for this, as a previous study found only minor effects of scanner type on the geometry of derived polygon surfaces (Colman et al. ). If there was artefactual variance caused by CT scanning and volume reconstruction, this would be incorporated in the factor ‘specimen’ in the permanova .…”
Section: Methodsmentioning
confidence: 99%
“…Voxel size has had a considerable effect on measurements and the effect of the segmentation method seemed to increase with voxel size (Christiansen, 2016). Scanner type and imaging conditions have affected the geometry of surfaces generated from CT scans, although the effects have been small compared with the variance introduced by manual segmentation (Colman et al 2017). All the factors influencing the segmentation results and the geometry of a CT-derived surface potentially contribute to measurement error in landmark data obtained from such surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Data acquired from a clinical radiological setting is actually a more accurate representation of the current population than most body donation programs since it is less affected by secular trends and age bias. Furthermore, reconstructions that are based on the CT scan data can provide a precise three-dimensional (3D) model that represents the original skeletal element [23]. However, in order for CT scans to be a feasible alternative to traditional skeletal collections, the morphological traits indicating sex also need to be accurately portrayed in the 3D reconstructions and their associated sex estimation scores need to correspond to the scores recorded on the dry skeletal element.…”
Section: Introductionmentioning
confidence: 99%